Ergonomic Evaluation in Public Transport Particularly in Public Transportation with an Anthropometric Approach in Tegal City: Enhancing Comfort and Safety in Urban Transportation through Anthropometric Design Adjustments - Putri, Nazwa Febryana; brilianti, Dani Fitria (Kirana Publisher (KNPub), 2024)
Public transportation plays an important role in facilitating portability, especially in urban areas. In Tegal City, public transportation is an important mode of transportation for its citizens. However, ergonomic assessments of public transport vehicles are often neglected, resulting in potential discomfort and welfare issues for passengers and drivers. This research evaluates the ergonomic design of public transportation using an anthropometric approach to adapt vehicle dimensions to the user's physical needs, such as seating, legroom and accessibility. The results of the analysis provide recommendations for improvements, including increased ventilation, seat adjustments and safety features, to create a more comfortable and safer transportation system. By collecting and analyzing anthropometric information from agent testing results on clients in Tegal City, this research asks questions to identify the imbalance between the physical size of public transportation and the needs of its users. It is hoped that these findings will suggest changes to the plan that increase comfort, reduce fatigue, and improve general well-being. It will also contribute to a broader understanding of how ergonomic standards can be linked to open transport frameworks to improve client experience and safety.